Development of a human mitochondrial oligonucleotide microarray (h-MitoArray) and gene expression analysis of fibroblast cell lines from 13 patients with isolated F1Fo ATP synthase deficiency - Čížková, Alena; Stránecký, Viktor; Ivánek, Robert; Hartmannová, Hana; Nosková, Lenka; Piherová, Lenka; Tesařová, Markéta; Hansíková, Hana; Honzík, Tomáš; Zeman, Jiří; Divina, Petr; Potocká, Andrea; et al. (BMC genomics, 2008)
BACKGROUND: To strengthen research and differential diagnostics of mitochondrial disorders, we constructed and validated an oligonucleotide microarray (h-MitoArray) allowing expression analysis of 1632 human genes involved in mitochondrial biology, cell cycle regulation, signal transduction and apoptosis. Using h-MitoArray we analyzed gene expression profiles in 9 control and 13 fibroblast cell lines from patients with F1Fo ATP synthase deficiency consisting of 2 patients with mt9205deltaTA microdeletion and a genetically heterogeneous group of 11 patients with not yet characterized nuclear defects. Analysing gene expression profiles, we attempted to classify patients into expected defect specific subgroups, and subsequently reveal group specific compensatory changes, identify potential phenotype causing pathways and define candidate disease causing genes. RESULTS: Molecular studies, in combination with unsupervised clustering methods, defined three subgroups of patient cell lines--M group with mtDNA mutation and N1 and N2 groups with nuclear defect. Comparison of expression profiles and functional annotation, gene enrichment and pathway analyses of differentially expressed genes revealed in the M group a transcription profile suggestive of synchronized suppression of mitochondrial biogenesis and G1/S arrest. The N1 group showed elevated expression of complex I and reduced expression of complexes III, V, and V-type ATP synthase subunit genes, reduced expression of genes involved in phosphorylation dependent signaling along MAPK, Jak-STAT, JNK, and p38 MAP kinase pathways, signs of activated apoptosis and oxidative stress resembling phenotype of premature senescent fibroblasts. No specific functionally meaningful changes, except of signs of activated apoptosis, were detected in the N2 group. Evaluation of individual gene expression profiles confirmed already known ATP6/ATP8 defect in patients from the M group and indicated several candidate disease causing genes for nuclear defects. CONCLUSION: Our analysis showed that deficiency in the ATP synthase protein complex amount is generally accompanied by only minor changes in expression of ATP synthase related genes. It also suggested that the site (mtDNA vs nuclear DNA) and the severity (ATP synthase content) of the underlying defect have diverse effects on cellular gene expression phenotypes, which warrants further investigation of cell cycle regulatory and signal transduction pathways in other OXPHOS disorders and related pharmacological models.
Keywords: analýza hlavních komponent; Mitochondrial Diseases; Humans; Mitochondrial Proton-Translocating ATPases; genom mitochondriální; mitochondriální DNA; Oligonucleotide Array Sequence Analysis; Genome, Mitochondrial; DNA, Mitochondrial; financování organizované; Cluster Analysis; Phenotype; Financing, Organized; lidé; Sequence Deletion; Principal Component Analysis; mitochondriální protonové ATPasy; buněčné linie; sekvenční delece; Cell Line; modely genetické; fenotyp; stanovení celkové genové exprese; shluková analýza; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Models, Genetic; fibroblasty; mitochondriální nemoci; Gene Expression Profiling; Fibroblasts